Access to Safety for Domestic Workers in Indonesia - Pramesti, Fahrinda Khansa; Sa'adah, Nabiatatus (Pandecta Research Law Journal, 2024)
Domestic workers are one of the informal workers in Indonesia who work for individuals in the household who do household work. The constitutional basis for the protection of every worker, including domestic workers, as regulated in Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia is that every citizen has the right to work and a living worthy of humanity. Article 1 of the Minister of Manpower Regulation Number 2 of 2015 explains that a Domestic Worker (PRT) is someone who works for an individual in a household to carry out household work by receiving wages and/or other forms of compensation. This research aims to analyze the urgency of work safety for domestic workers in Indonesia and determine the implementation of legal protection for domestic workers in gaining access to work safety. This research method uses normative juridical. Occupational safety and health are procedures that exist in work, covering the whole, namely not only the occupants of the house but there are conditions and factors that have an impact on the safety and health of both domestic workers and people in the workplace. From the research results, it can be concluded that with the potential for danger, it is necessary to regulate Occupational Safety and Health (K3) for domestic workers to create comfortable, effective and safe conditions.